KETEPATAN PENGGUNAAN SITASI DALAM ARTIKEL ILMIAH - Muthia Ayyuni Helmi; Djogi Hot Jonathan Siburian; Triaviranda; Wanti Br Hombing; Thomas Manurung; Nurul Azizah (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
Accurate citation is an important element in scientific writing because it relates to academic integrity, source transparency, and the credibility of a scientific work. This study aims to identify various forms of citation errors found in scientific articles and explain their impact on the academic quality of writing. The research method used is a qualitative approach with a literature review type of research. The research data was obtained from several scientific articles in the fields of education and Indonesian language published in the last five to ten years. The data collection technique was carried out through documentation studies, while data analysis used content analysis techniques, which included data reduction, categorization, interpretation, and descriptive data presentation. The results of the study show that there are still various errors in the use of citations in scientific articles, including errors in the format of citation writing, inconsistencies between quotations in the text and the bibliography, references that cannot be found, and quotations that are not relevant to the content of the discussion.